2017
DOI: 10.1016/j.addbeh.2017.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Motivational Interviewing Treatment Integrity coding system 4.2 with jail inmates

Abstract: Motivational Interviewing (MI) is an evidence-based approach shown to be helpful for a variety of behaviors across many populations. Treatment fidelity is an important tool for understanding how and with whom MI may be most helpful. The Motivational Interviewing Treatment Integrity coding system was recently updated to incorporate new developments in the research and theory of MI, including the relational and technical hypotheses of MI (MITI 4.2). To date, no studies have examined the MITI 4.2 with forensic po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 22 publications
(31 reference statements)
1
14
0
Order By: Relevance
“…Additionally, 80% of the rated sessions fulfilled the benchmark for good MI on the relational summary score, 67% for the technical summary score, 76% of the rated sessions fulfilled benchmarks for the summary score of percent complex reflections, and 47% of rated session the reflection to question ratio. All in all, these indicate high levels of fidelity and are comparable to other studies with high levels of fidelity to MI (Boman et al, 2018;Freira et al, 2018;Magill, Graves, et al, 2018;Owens et al, 2017;Serrano et al, 2017) and substantially higher than studies with expected lower fidelity to MI (Copeland et al, 2018;Simper, Breckon, and Kilner, 2017). The ratings indicated use of MIA's, but the general low ratings of emphasize autonomy questions the use of this important MI-technique in this study.…”
Section: Fidelity To MIsupporting
confidence: 85%
See 2 more Smart Citations
“…Additionally, 80% of the rated sessions fulfilled the benchmark for good MI on the relational summary score, 67% for the technical summary score, 76% of the rated sessions fulfilled benchmarks for the summary score of percent complex reflections, and 47% of rated session the reflection to question ratio. All in all, these indicate high levels of fidelity and are comparable to other studies with high levels of fidelity to MI (Boman et al, 2018;Freira et al, 2018;Magill, Graves, et al, 2018;Owens et al, 2017;Serrano et al, 2017) and substantially higher than studies with expected lower fidelity to MI (Copeland et al, 2018;Simper, Breckon, and Kilner, 2017). The ratings indicated use of MIA's, but the general low ratings of emphasize autonomy questions the use of this important MI-technique in this study.…”
Section: Fidelity To MIsupporting
confidence: 85%
“…The fourth revision of the MITI incorporated the empirical literature, indicating the importance of the therapist's role in both encouraging change, favoring language from the client (Change Talk) and decreasing language opposing change (Sustain Talk) in MI treatment sessions. The new measures of the MITI 4 has acceptable reliability (Moyers et al, 2016;Copeland et al, 2018;Kramer Schmidt, Andersen, Nielsen, and Moyers, 2019;Owens, Rowell, and Moyers, 2017;Serrano et al, 2017) and validity when comparing them to the golden standard, the MISC (Motivational Interviewing Skills Code) (Moyers et al, 2016).…”
Section: The Motivational Interviewing Treatment Integrity Code (Miti)mentioning
confidence: 99%
See 1 more Smart Citation
“…The MITI is recently refined to reflect the developments in the theory of MI and to improve reliability of the measures (MITI 4) (Moyers et al, 2014). The MITI 4 has been applied in some studies so far supporting the reliability to MI and to some extend the validity (Copeland et al, 2019;Moyers et al, 2016;Owens et al, 2017;Serrano, 2018). The MITI 4 provides information on the technical elements of MI by means of a measure of the therapist's ability to cultivate change talk and soften sustain talk; the relational elements empathy and partnership; in addition, detailed information on MI-adherent therapist behavior (affirmation, seeking collaboration, emphasizing autonomy) and MI-non-adherent therapist adherent (confront and persuade) (Moyers et al, 2014) is collected.…”
Section: Instrument To Measure Elements Of MImentioning
confidence: 96%
“…Even though this could be due to differences within the therapist as well, it is in line with the findings of participant characteristics affecting MI delivery. For instance, participant characteristics like criminal history (Owens et al, 2017), severity of addiction (Imel et al, 2011), and level of motivation for change (Gibbons et al, 2010;Imel et al, 2011) have been found to affect how MI is delivered. Thus, in order to attempt to compare the delivery of MI across countries, the therapists in the various nations should, as a minimum, treat individuals with similar characteristics and problems.…”
Section: Introductionmentioning
confidence: 99%